Pengembangan Media Pembelajaran Pendidikan Pancasila Berbasis Android (Studi Pada Fase F di SMA Negeri 1 Surakarta) - Zumrotul Muadzimah; Wijianto; Widya Noventari (Universitas Negeri Semarang, 2025)
The aim of this research is to develop media and determine the level of feasibility of Android-based Pancasila Education learning media products. This type of research is included in research and development. The development model used in this research is the Sukmadinata model. The Sukmadinata model consists of three steps, namely preliminary study, development and testing. This research data was obtained from media expert validation questionnaires, materials and student pre-test and post-test results. The Android-based learning media that was developed was then validated by material expert validators and media experts to provide an assessment regarding the suitability of the learning media. Next, it is tested on students. The purpose of the trial was to determine the difference in use of classes that were treated and classes that were not treated. The research results showed that Android-based learning media was declared very feasible at 87.7% for material validation and 81.4% for media validation. This study highlights how the integration of digital applications can increase the effectiveness of the teaching and learning process, both in terms of student involvement and learning outcomes.